Nanotechnology-Based Cardiac Targeting and Direct Cardiac Reprogramming: The Betrothed. (11th December 2017) - Passaro, Fabiana; Testa, Gianluca; Ambrosone, Luigi; Costagliola, Ciro; Tocchetti, Carlo Gabriele; di Nezza, Francesca; Russo, Michele; Pirozzi, Flora; Abete, Pasquale; Russo, Tommaso; Bonaduce, Domenico
Abstract : Cardiovascular diseases represent the first cause of morbidity in Western countries, and chronic heart failure features a significant health care burden in developed countries. Efforts in the attempt of finding new possible strategies for the treatment of CHF yielded several approaches based on the use of stem cells. The discovery of direct cardiac reprogramming has unveiled a new approach to heart regeneration, allowing, at least in principle, the conversion of one differentiated cell type into another without proceeding through a pluripotent intermediate. First developed for cancer treatment, nanotechnology-based approaches have opened new perspectives in many fields of medical research, including cardiovascular research. Nanotechnology could allow the delivery of molecules with specific biological activity at a sustained and controlled rate in heart tissue, in a cell-specific manner. Potentially, all the mediators and structural molecules involved in the fibrotic process could be selectively targeted by nanocarriers, but to date, only few experiences have been made in cardiac research. This review highlights the most prominent concepts that characterize both the field of cardiac reprogramming and a nanomedicine-based approach to cardiovascular diseases, hypothesizing a possible synergy between these two very promising fields of research in the treatment of heart failure.